DISINFORMATION AS A TOOL OF HYBRID WARFARE: ESSENCE AND CONSEQUENCES - Krikun, Vitaly; Baulina, Tamila (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2022)
The article examines a number of issues related to the specifics of information dissemination under the conditions of communicative practice of both an individual level and the functioning of mass media. The main attention is paid to the issue of the deliberate spread of disinformation. In this context, the phenomenon of "hybrid war" and the place of the information component in it, the issue of using narratives as an effective means of mass information damage, and the specifics of the process of "devaluation of the word". The need to develop mechanisms to counteract the phenomena of "abuse of freedom of speech" and "simulative democracy" to ensure the survival and sustainable development of democratic societies is substantiated.